Upskilling Malaysia’s Nursing Workforce - Wong, Lee Sia *; Harjit, Kaur *; Sawnthary, Malluvalasa *; Chee, Gek Neo * (Social Health Analytics Sdn Bhd, 2023)
By championing opportunities and cultivating a culture that esteems persistent education, we can sculpt nurses who aren’t just adept, but can also emerge as health care trailblazers.